From ideology to liturgy : Reconstructionist worship and American liberal Judaism - Caplan, Eric, 1963- (Monographs of the Hebrew Union College, 2022)
"This study examines Reconstructionism's interpretation and adaptation of the traditional Jewish liturgy and creation of new prayer texts to convey and express its changing ideology. Other branches of American liberal Judaism are examined as well. All facets of the movement's liturgical materials are analysed, including translations, rubrics and layout"--